Improving students' writing skills by using fables / Khairunisa Nikman, Juhaida Abdul Aziz and Amiza Mohd Salleh - Nikman, Khairunisa; Abdul Aziz, Juhaida; Mohd Salleh, Amiza (2011)
To many teachers, poor writing skill is a worrying problem among the students and many also view writing as the most difficult language skill to acquire. Currently, many children are fortunate to be taught using methods that embrace their right-brain creativity and some educators have discovered greater potentials for better writing by learning what they can from every situation using fables. The aim of this research was to investigate the level of effectiveness of using fables as a tool to enhance students' performance in writing. The findings reveal that the students are interested in using fables to learn writing, thus they participated well in all the activities using the fables. The increase in performance when comparing the pre-test scores with the post-test scores also proved that the activities carried out using the fable had helped the respondents to write more creatively.